Perancangan dan Implementasi Sistem Informasi Penjualan Handphone Berbasis Web Menggunakan Framework Laravel - Yakobus Kevin Dean Prasetyo; Eko Sediyono (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Tatto Cellular is a business entity located in Tegal, which is engaged in selling cellphones. Tatto Cellular has problems with ordering goods, because currently sales are still manual. The purpose of this research is to produce an online store website with the Laravel framework that can be used to sell new and old cellphones. The process of designing an online shop website on Tatto Cellular uses the Laravel framework. System modeling uses UML. Data collection methods used in this study are interviews and observation. The results of this study are to produce an online shop website software at Tatto Cellular using the Laravel framework which functions to expand product marketing and make shopping faster and more convenient for consumers without having to come directly to the store.